Diseño y creación de una red de pastelería especializada (2016)
Given that, market for bakery products and pastries must be revolutionized day by day to offer new alternatives for all economic sectors, the idea of creating a retail public in lower socioeconomic stratum, based on the familiar experience of 31 years in the sector bakery, family financial support, with an establishment called Panadería y Pastelería Espysan, founded on 17 March 1984 by Orlando Espinosa Alvarado. Allegra bakery opens on September 17, 2016, an establishment focused on the production and sale of cakes and cakes for low socioeconomic stratum, since there are no such pastry shops in these areas. This first point is in a shop in the Quintanares (Soacha) neighborhood. It has two floors: production area on the second floor, care and retail on the first floor. It has a refrigerator, display cases for greater attention from customers and a comfortable area for customers to consume the products into the pastry.